The Effect of Self-Awareness and Problem-Solving Skills Training Based on Edugames on Burnout in Midwives - Novita, Novita; Lindayani, Linlin; Mutiar, Astri; Darmawati, Irma (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study aimed to determine the effect of edugame-based self-awareness and problem-solving skill training on burnout in midwives. Methods: The study used a repeated measurement-quasi-experiment design in a hospital in Bekasi, West Java, with 120 midwives in both groups. Results: Emotional exhaustion (Eta = 0.05, p = 0.443), depersonalization, (Eta = 0.03, p = 0.718) and personal accomplishment scores (Eta = 0.08, p = 0.694) did not change significantly in the control group. At the same time, interventions reduced the total score of emotional exhaustion (Eta = 0.26, p = 0.001), depersonalization (Eta = 0.20, p = 0.010), and personal accomplishment (Eta = 0.35, p = 0.001). Conclusions: Midwives were more likely to accept their emotional exhaustion after intervention, were able handle depersonalization and performed personal accomplishment. The study underscores the significance of midwives' self-awareness and problem-solving skills in identifying burnout symptoms, advocating for change, and providing necessary support services.